Coulomb blockade of spin-dependent shuttling - Park, Hee Chul; Kadigrobov, Anatoli M.; Shekhter, Robert I.; Jonson, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
We show that nanomechanical shuttling of single electrons may enable qualitatively new functionality if spin-polarized electrons are injected into a nanoelectromechanical single-electron tunneling (NEM-SET) device. This is due to the combined effects of spin-dependent electron tunneling and Coulomb blockade of tunneling, which are phenomena that occur in certain magnetic NEM-SET devices. Two effects are predicted to occur in such structures. The first is a reentrant shuttle instability, by which we mean the sequential appearance, disappearance and again the appearance of a shuttle instability as the driving voltage is increased (or the mechanical dissipation is diminished). The second effect is an enhanced spin polarization of the nanomechanically assisted current flow.